2014
DOI: 10.1039/c3tb21379j
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of a pH sensitive nanomedicine using doxorubicin loaded poly(aspartic acid-graft-imidazole)-block-poly(ethylene glycol) micelles

Abstract: A polyelectrolyte block copolymer, poly(aspartic acid-graft-imidazole)-block-poly(ethylene glycol) (P(Aspg-Im)-PEG), with several advantages such as an easy synthesis, having a high molecular weight and the buffer capacity of a zwitterionic polymer backbone compared to poly(histidine) backbones, was presently investigated to evaluate its feasibility as a pH sensitive anticancer nanomedicine. Doxorubicin (DOX) loaded P(Asp-g-Im)-PEG micelles (DPHAIM) were prepared by the bottom flask and diafiltration methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
(58 reference statements)
2
23
0
Order By: Relevance
“…These suggested that the acidic pH condition could trigger the drug release from PIC and the increased dox near MCF-7 cells could enhance the anticancer toxicity. 19 These drug release profiles and cell viability support the notion that PIC may be useful for targeting cancer microenvironment-associated pH, and be considered for the triggering of drug release at endosomal/ lysosomal pH.…”
Section: Development Of a Ph-dependent Nanomedicinesupporting
confidence: 60%
See 1 more Smart Citation
“…These suggested that the acidic pH condition could trigger the drug release from PIC and the increased dox near MCF-7 cells could enhance the anticancer toxicity. 19 These drug release profiles and cell viability support the notion that PIC may be useful for targeting cancer microenvironment-associated pH, and be considered for the triggering of drug release at endosomal/ lysosomal pH.…”
Section: Development Of a Ph-dependent Nanomedicinesupporting
confidence: 60%
“…pH-sensitive nanosystems could be used as a cancer reversal strategy through the exploitation of their favorable properties such as improved stability at physiological pH, reduced toxicity, and the controlled release of therapeutic agents at extracellular tumor pH (pH ex =~6.5-7.2) or endosomal pH (pH en #6.5). 18,19 Here, a PIC based on PEG-PLA-PEI and P(Asp) was evaluated for its pH-sensitive anticancer nanomedicinal potential using doxorubicin (dox) as an anticancer model drug.…”
mentioning
confidence: 99%
“…40% maximum cumulative release over 24 h, whereas pH 6.5 led to a drastic enhancement of DOX release from NC 2. This might be attributed to altered interaction between imidazolium and carboxylate in the P(Asp-g-Im) block to form the pH-dependent NC core [43,49]. At pH levels above 7.4, NC 2 formed a stable nano-assembly with DOX, hydrophobic P (Asp-g-Im) block cores, and hydrophilic PEG coronas.…”
Section: Nc Characterizationmentioning
confidence: 99%
“…Lee et al 15 designed pH-responsive intelligent microspheres Doxorubicin (DOX) loaded P(Asp-g-Im)-PEG micelles (DPHAIM, Figure 1 ) for the weakly acidic tumor microenvironment. With aspartic acid imidazole as the hydrophobic group and ethylene glycol as the hydrophilic group, the formed copolymer P(Aspg-Im)-PEG can load up to 28% DOX.…”
Section: Tumor Targeting By Nanoparticlesmentioning
confidence: 99%